Identification and Antimicrobial Resistance of Campylobacter Species Isolated from Animal Sources - Marinou, Ioanna; Bersimis, Sotiris; Ioannidis, Anastassios; Nicolaou, Chryssoula; Mitrousia-Ziouva, Angeliki; Legakis, Nicholaos J.; Chatzipanagiotou, Stylianos (Frontiers in Microbiology, 2012)
Background:Campylobacter spp. are together with Salmonella spp. the leading causes of human bacterial gastroenteritis worldwide. The most commonly isolated species in humans are Campylobacter jejuni and C. coli The isolation, identification and antimicrobial resistance of Campylobacter spp. from poultry and raw meat from slaughterhouses, has been investigated for the first time in Greece. During the period from August 2005 to November 2008 a total of 1080 samples were collected: a) 830 fecal samples from five poultry farms, b) 150 cecal samples from chicken carcasses in a slaughterhouse and c) 100 fecal samples from one pig farm near the region of Attica. The identification of the isolates was performed with conventional, as well as with and molecular methods. Results: Sixteen Campylobacter strains were isolated, all from the poultry farms. None of the strains was identified as C. jejuni. Antimicrobial susceptibility to six antimicrobials was performed and all the strains were susceptible to ciprofloxacin, amoxicillin-clavulanic acid and gentamicin. Thirteen out of 14 C.coli were resistant to erythromycin and all C.coli strains were resistant to ampicillin. Conclusions:Our results emphasize the need for a surveillance and monitoring system with respect to the prevalence and antimicrobial resistance of Campylobacter in poultry, as well as for the use of antimicrobials in veterinary medicine in Greece.